Forming the future teacher's readiness for continuous professional and personal development - V. N. Mezinov (Вестник Северо-Кавказского федерального университета)
In connection with the modernization of the professional training of the future teacher, the problem of orientation of modern education to the continuous professional and personal development of the student, the innovative combination of modern technologies and digital tools that contribute to the progress and quality of training and professional education becomes urgent. The purpose of the article is to carry out a theoretical analysis of the phenomenon of a teacher's readiness for continuous professional and personal development, clarify the terminology of related concepts, identify conditions that ensure the effectiveness of the phenomenon under study, and present the results of empirical research. 178 students of Yelets State University took part in the study. The assessment of the future teacher's readiness for continuous professional and personal self-improvement was carried out on the basis of a survey, expert assessments and observation. The revealed effective methods, technologies, means and conditions of training contribute to positive dynamics of the formation of components of the professional and personal development of the future teacher. It is concluded that the decisive moment for the professional and personal development of a future teacher is the establishment of the personal meaning of pedagogical activity.